Упростить выражение: (1-cos² a) (1+ctg² a)

Упростить выражение: (1-cos² a) (1+ctg² a)
Гость
Ответ(ы) на вопрос:
Гость
1/cos^2(a)-1/ctg^2(a)=1/cos^2(a)-tg^2(x)=1/cos^2(x)-sin^2(x)/cos^2(x)=1-sin^2(x)/cos^2(x)=cos^2(x)/cos^2(x)=1  a)1. ОДЗ: ctga≠0 cosa≠0 a≠пn a≠п/2+2пn n∈z 1-sina/1+sina-1-2sina/cos^2(a)=1-sina/1+sina-1-2sina/1-sin^2(a)=1-sina/1+sina-1-2sina/(1-sina)*(1+sina)=((1-sina)*(1-sina)-1+2sina)/(1-sina)*(1+sina)=(1-2sina-sin^2(a)-1+2sina)/(1-sina)*(1+sina)=sin^2(a)/cos^2(a)=tg^2(a) ОДЗ: sina≠-1 cosa≠0 a≠-3п/4+2пn a≠п/4+пn n∈z
Не нашли ответ?
Ответить на вопрос
Похожие вопросы